METODOLOGI TAFSIR AHKAM BEBERAPA PENDEKATAN DAN ALIRAN DALAM MENGETAHUI MAQASHID AL-SYARIAH (STUDI PERBANDINGAN) - Wahyuni, Afidah (IBN KHALDUN BOGOR, 2014)
Methodology Commentary Ahkam. The perfection of Islam is not the explanation lies in the Qur'an in detail to every problem facinghumanity, but on abortion that contain the basic tenets and principal. For if the Qur'an as a major source of Islamic teachings explain in detail to all the problems facing humanity, then Islam will lose relevance with the community dynamics are constantly changing from time to time. Therefore, the verses of the Koran are generally only contain teachings in the form of basic and fundamental, without further explanation about the details and procedures for implementation. Then the Sunnah of the Prophet provide an explanation of the details and procedures for the implementation of the basic teachings.